PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT (POS) & PENGAWASAN TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING PADA PT. HUTAHAEAN GROUP PEKANBARU - Madeline Mercy; Ningsih Suryati Dewita; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The aim of this research is to determine the effect of Perceived Organizational Support and Supervision with Organizational Citizenship Behavior as an Intervening variable at PT. Hutahaean Group Pekanbaru. Primary data was collected through a questionnaire as a tool to prove the results of the research. Data analysis techniques in this study is using Path Analysis. The sampling technique is a method that has been selected census (60 employees at PT. Hutahaean Group Pekanbaru). The results showed that : 1) Perceived Organizational Support had a positive and significant effect on Organizational Citizenship Behavior 2) Perceived Organizational Support had a positive and significant effect on employee performance 3) Supervision had a positive and significant effect on Organizational Citizenship Behavior 4) Supervision had a positive and significant effect on performance employees 5) Organizational Citizenship Behavior has a positive and significant effect on employee performance 6) Perceived Organizational Support indirectly through Organizational Citizenship Behavior as an intervening variable has a significant effect on employee performance 7) Indirect supervision through Organizational Citizenship Behavior as an intervening variable has a significant effect on performance employee.Keywords: Perceived Organizational Support, Supervision, Organizational Citizenship Behavior, Employee Performance.